Digital Innovations and Technological Sovereignty - Ina Schieferdecker; Christoph March (Wirtschaftsdienst)
Abstract Digital innovations are changing our economies and societies. Shaping this transformation in line with core societal values and in a continual exchange with society is a key political challenge. The authors argue that technological sovereignty lies at the heart of this challenge. Rather than the autarchy from foreign technologies, this comprises the ability to define and establish core requirements on and properties of technologies, which safeguard the self-determination of citizens in the digital age. The authors show how an integrated innovation policy, which rests upon European collaboration and combines the promotion of technology development, technology transfer and individuals’ competencies, can achieve this goal.